Encalhes de tetrápodes marinhos e sua relação com variáveis meteorológicas e oceanográficas - Brusius, Bruna Kist (2019)
Stranding is the term used to refer to an animal that is found on land and does not have the ability to return to the sea. Stranded animals are frequently seen on the beaches around Brazil and the reasons that leads to this are multiples, varying from anthropic and fishery influences, diseases and marine pollution to storms occurrences that generate intense winds and higher wave heights. This phenomes can affect the species survivor, leading them to exhaustion, affecting its movements and food search. The present study aims a better comprehension of the effects of meteorological and oceanographic variables on the marine tetrapod stranded found on Ilha Comprida, southern coast of São Paulo State between 1998 and 2016. Data from dead marine animals stranded were obtained from weekly surveys of the Ilha Comprida beaches and divided on six groups: marine mammals, sea turtles, resident seabirds, seabirds visitors from the North, seabirds visitors from the South and Spheniscus magellanicus (Magellanic penguins). The meteorological and oceanographic variables were: significant wave height (SWH), mean sea level pressure (MSLP), wind intensity (WI), wind direction (WD) and sea surface temperature (SST). The methodology consisted on preliminary analysis of correlation between the stranded data and the variables, followed by multiple regressions using generalized linear models (GLM) with a binomial distribution. Besides that, for the major stranded events, synoptic maps of MSLP, WI, WD and oceanic maps of SWH were analyzed apart. The results found on the present study demonstrated a relation between the species presence on the region, both by its migratory period or by the foraging time and the food abundance. The seabird visitors from the South and the Magellanic penguin were the groups that presented the highest numbers of stranded animals. According to the GLM analyzes were observed that different groups were influenced by different variables, but the variables that presented an annual cycle well defined, as MSLP and SST showed a more significant relation with the strandings. The highest events of strandings, according to the synoptic and oceanic maps, showed relation with transient high-pressure systems, which produce wind on the direction of the beach and also with cold front passages on the study area. The results obtained here adding new knowledge over the elements that can lead to marine animal strandings on the southern of the São Paulo State, mainly the non-anthropogenic factors.